Herpes simplex virus type 2 acquisition among HIV-1-infected adults treated with Tenofovir disoproxyl fumarate as part of combination antiretroviral therapy: Results from the ACTG A5175 PEARLS study - Celum C. (2017)
© The Author 2017. Published by Oxford University Press for the Infectious Diseases Society of America. Objective: Tenofovir disoproxyl fumarate (TDF) disoproxyl fumarate (TDF) has in vitro activity against herpes simplex virus type 2 (HSV-2) and reduced HSV-2 acquisition as preexposure prophylaxis. Whether TDF-containing antiretroviral therapy (ART) reduces HSV-2 acquisition is unknown. Design: Secondary analysis of AIDS Clinical Trials Group A5175, a randomized, open-label study of 3 ART regimens among 1571 participants. Methods: HSV-2 serostatus was assessed at baseline, at study exit, and before a change in ART regimen. Results: Of 365 HSV-2-seronegative persons, 68 acquired HSV-2, with 24 receiving TDF-containing ART and 44 receiving ART without TDF (HSV-2 seroconversion incidence, 6.42 and 6.63 cases/100 person-years, respectively; hazard ratio, 0.89; 95% confidence interval,.55-1.44). Conclusions: HSV-2 acquisition was not reduced in HIVinfected, HSV-2-uninfected persons during TDF-containing ART.